Effect of the back plate position on the kick-start performance of competitive swimmers - Sakai, S.; Takeda, T.; Sato, S.; Tsubakimoto, S.; Takagi, H. (Japan Journal of Physical Education, Health and Sport Sciences, 2017)
In a competitive swimming race event, the back plate can be placed on the starting block. Although the back plate has different setting positions, the effect of the plate position on start performance has not yet been clarified. This study was conducted to investigate the effect of the back plate position on the kick-start performance of competitive swimmers. Six male swimmers dived from an instrumented starting block that contained two force plates and force sensors to measure the reaction forces exerted by the hands and front and rear feet. Four high-speed cameras were used to obtain kinematic data on the swimmers. The horizontal take-off velocity of the front plate position resulted in a better outcome than the back plate position (p<0.05). In the front plate position, a longer rear foot contact time generated a large impulse, and swimmers were able to achieve a higher take-off velocity. To generate a larger impulse, the contact time on the starting block needed to be longer. However, swimmers were able to achieve a higher take-off velocity using the front plate position without extending the block time. In this manner, the front plate position did not affect the time on the block. Moreover, different setting positions of the back plate influenced the joint angle of the postural set before the starting signal. Differences in the joint angle led to an increase in the horizontal component of the force impulse of the rear leg. Therefore, revealing the relationship between the joint angle of the postural set and start performance would provide detailed information on the optimum start posture for swimmers, including the plate position.